2014
DOI: 10.1097/psy.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-Day Dynamics of Associations Between Sleep, Napping, Fatigue, and the Cortisol Diurnal Rhythm in Women Diagnosed as Having Breast Cancer

Abstract: OBJECTIVES To examine whether day-to-day variations in sleep behaviors, ongoing sleep disturbance and fatigue predict the cortisol diurnal rhythm in women recently diagnosed with early stage breast cancer. Methods Women (N=130, age=55. 6±9.4 years) collected saliva 5×/day/2 days for cortisol. Diaries were used to assess prior-day nap duration, nocturnal awakenings, sleep latency, and morning restfulness. Ongoing fatigue and sleep disturbance were measured using the Multidimensional Fatigue Symptom Inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
2
31
1
Order By: Relevance
“…To our knowledge only two studies specifically investigated this issue in breast cancer patients (n=29 and n=130, respectively) and results are still inconclusive [12][13][14]. Therefore, we investigated the association between diurnal cortisol pattern and the different dimensions of fatigue in a large sample of breast cancer patients (n=265) undergoing chemo-or radiotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…To our knowledge only two studies specifically investigated this issue in breast cancer patients (n=29 and n=130, respectively) and results are still inconclusive [12][13][14]. Therefore, we investigated the association between diurnal cortisol pattern and the different dimensions of fatigue in a large sample of breast cancer patients (n=265) undergoing chemo-or radiotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…These sleep problems were characterized by prolonged sleep onset latency (M= 54.3, SD= 49.2 minutes) and frequent nighttime awakenings, despite 40% of the patients using sleep medications three or more times a week [16]. Greater ongoing fatigue or sleep disturbance predicted a slower cortisol decline, and longer sleep latency predicted both a greater cortisol linear decline and slower cortisol decline [9]. Several studies elucidate how the sleep quality changed during cancer treatments such as chemotherapy or radiotherapy.…”
Section: How Is the Sleep Quality In Women With Breast Cancer?mentioning
confidence: 99%
“…Studies using the PSQI documented poor sleep quality for 65% to 70% of the participants [4,28] and, actigraphy verified that up to 87% of the sample had an excessive number of awakenings.13Moreover, sleep diary records identified that difficulty maintaining sleep was evident by the higher than normal (2-6) number of awakenings per night (6)(7)(8)(9)(10)(11)(12) [27].…”
Section: How Is the Sleep Quality In Women With Breast Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sleep disturbances appear to be associated also with a disrupted cortisol rhythm. For instance, in women with breast cancer, sleep disturbances and feeling less rested in the morning predicted lower awakening cortisol and a slower cortisol decline, suggesting an association between a dysregulation of the HPA axis and sleep dysfunction 204 .…”
Section: Sleep Dysfunction As a Target In Cancer-related Depressionmentioning
confidence: 99%